Priority Analysis of Road Infrastructure Development in the Mandalika Special Economic Area: Application of Analytic Network Process (ANP) and Topsis Methods - Lalu Andri Tanuwijaya; Jauhar Fajrin; I Ketut Budastra (Riviera Publishing, 2025)
The Mandalika Special Economic Zone (KEK) is key to Indonesia's economic growth. Located in southern Lombok Island, it became a Tourism SEZ via Government Regulation Number 52 of 2014. However, infrastructure development in Mandalika SEZ faces challenges, notably low investment returns. Choosing the right roads is crucial, requiring effective decision-making to attract investors and promote regional development in Central Lombok. This research used literature review and data collection through interviews and questionnaires to assess road development criteria. The Analytic Network Process (ANP) and TOPSIS methods prioritized infrastructure development. Four key criteria were identified: Tourism Infrastructure, Costs, Investor Interest, and Average Daily Traffic. The study ranks road segments for Mandalika SEZ, with the Circuit's Southern Ring Road (P5 - I1) as the top priority. This MCDA-derived prioritization provides actionable insights for policymakers and investors, enhancing strategic infrastructure investments to boost economic impact and support sustainable tourism growth. The findings validate the integration of ANP and TOPSIS in regional development planning.